Animal Life Cycle Media Using Digital Comics for Fourth-Grade Elementary School Students - Yuswantara, I Kadek Jodi; Wibawa, I Made Citra (Universitas Pendidikan Ganesha, 2021)
The Covid-19 pandemic situation has an impact on various aspects of human life, one of which is education. The Covid-19 pandemic has caused a change in the process of organizing learning from face-to-face to online learning. This change makes the availability of learning media for elementary school students in participating in online learning to be limited. This study aims to develop an animal life cycle media using digital comics for fourth grade elementary school students. This research is a media development research using the ADDIE model. The pandemic situation causes research to only be carried out until the development stage. The subjects of this research are two material experts, two media experts and two practitioners, while the object of this research is the validity of animal life cycle media using digital comics. The analysis technique used is qualitative and quantitative analysis. The instrument for collecting data in this study was a rating scale questionnaire. The data obtained from the media validity test were analyzed to find the percentage score. The results of the media test obtained were the material expert test with a percentage of 97.33%, the media expert test with a percentage of 98% and the practitioner test with a percentage of 91%. The three test results received a very good predicate. It can be concluded that the animal life cycle media using digital comics is valid and feasible to be used as a learning medium in schools. Therefore, the animal life cycle media using digital comics can be used as an alternative online learning media for elementary school students.